2022
DOI: 10.3390/catal12091072
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Hydrogenation of Acetylene to Ethylene Catalyzed by Bimetallic CuNi/ZSM-12 Catalysts

Abstract: The purpose of this work is to develop a low-cost and high-performance catalyst for the selective catalytic hydrogenation of acetylene to ethylene. Non-precious metals Cu and Ni were selected as active ingredients for this study. Using ZSM-12 as a carrier, Cu-Ni bimetallic catalysts of CuNix/ZSM-12 (x = 5, 7, 9, 11) with different Ni/Cu ratios were prepared by incipient wetness impregnation method. The total Cu and Ni loading were 2 wt%. Under the optimal reaction conditions, the acetylene conversion was 100%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Previous studies on acetylene semihydrogenation to ethylene have shown that at a high H 2 /acetylene ratio, overhydrogenation of the formed ethylene leads to ethane formation. Hence, loss of reaction selectivity has been observed at high H 2 concentrations. , However, we do not expect this to happen for the UiO-67­(Co) cluster. Since the presence of adsorbed ethylene at the active site hinders H 2 bond dissociation, loss of reaction selectivity due to over hydrogenation seems unlikely.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Previous studies on acetylene semihydrogenation to ethylene have shown that at a high H 2 /acetylene ratio, overhydrogenation of the formed ethylene leads to ethane formation. Hence, loss of reaction selectivity has been observed at high H 2 concentrations. , However, we do not expect this to happen for the UiO-67­(Co) cluster. Since the presence of adsorbed ethylene at the active site hinders H 2 bond dissociation, loss of reaction selectivity due to over hydrogenation seems unlikely.…”
Section: Resultsmentioning
confidence: 82%
“…Hence, loss of reaction selectivity has been observed at high H 2 concentrations. 71,72 However, we do not expect this to happen for the UiO-67(Co) cluster. Since the presence of adsorbed ethylene at the active site hinders H 2 bond dissociation, loss of reaction selectivity due to over hydrogenation seems unlikely.…”
Section: Ethane Formation Via the Chch 3 Hydrogenationmentioning
confidence: 74%
See 1 more Smart Citation
“…In an attempt to replace Pd with an earth abundant metal, Hu et al created CuNi bimetallic catalysts of various ratios on ZSM-12 (pore window 6.0 × 5.6 Å) support. 66 First, they found that the combined bimetallic material had enhanced performance compared to its individual constituents. Fur-Figure 4.…”
Section: Synthesis Techniques and Their Impact On Catalyst Performancementioning
confidence: 99%
“…In an attempt to replace Pd with an earth abundant metal, Hu et al created CuNi bimetallic catalysts of various ratios on ZSM-12 (5.7 Å) support. 46 Firstly, they found that the combined bimetallic material had enhanced performance compared to its individual constituents. Furthermore, at an optimal temperature of 250°C with a Ni/Cu ratio of 7, 100% acetylene conversion could be achieved with 82.5% ethylene selectivity as compared to the Ni/ZSM-12 catalyst which only achieved ~70% selectivity at full acetylene conversion.…”
Section: Post Synthesis Techniquesmentioning
confidence: 99%